Urban scalograms: an experiment in scaling, emergence, and Greek and Roman urban form - Hanson, JW (Brepols Publishers, 2022)
Although there has been extensive research on urban form, including quantifying various aspects of settlements, there has been less consideration of why certain cities had certain features. In this article, I suggest a new method for investigating the relationship between the presence and absence of monuments and the sizes of settlements, before applying it to the Roman Empire. The results show that there is a strong relationship between both the numbers and diversities of buildings and the presence and absence of different monuments and the sizes of sites. This reveals not only how the constituent elements of the built environments of cities changed as they increased in size, but also what order structures emerged in, potentially indicating what features we would expect a city of a certain size to have.